Advertising and promotion : an integrated marketing communications approach - Hackley, Christopher E. (Los Angeles : SAGE, 2010)
This detailed and insightful text explains how advertising comes to cast its shadow over contemporary consumer culture. Case examples are used to illustrate the power of advertising to portray brand'personalities' in terms that resonate with consumers across many cultures.
Previous ed.: 2005.
Includes bibliographical references and index.
Keywords: Advertising; Advertising -- Social aspects; Sales promotion; Advertising -- Brand name products